Harry potters away - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Abiye Samuel Harry, who shares his Spore with more than fifteen other readers, is Principal Agricultural Officer in the River State Development Programme in Nigeria, and an avid user of Spore in his information work.'I responded to the article...